The construction of fatherhood the jurisprudence of the European Court of Human Rights - Margaria, Alice ca. 20./21. Jh (Cambridge University Press, 2019)
This book tackles one of the most topical socio-legal issues of today: how the law - in particular, the European Court of Human Rights - is responding to shifting practices and ideas of fatherhood in a world that offers radical possibilities for the fragmentation of the conventional father figure and therefore urges decisions upon what kind of characteristics makes someone a legal father. It explores the Court's reaction to changing family and, more specifically, fatherhood realities. In so doing, it engages in timely conversations about the rights and responsibilities of men as fathers. By tracing values and assumptions underpinning the Court's views on fatherhood, this book contributes to highlight the expressive powers of the ECtHR and, more specifically, the latter's role in producing and legitimising ideas about parenting and, more generally, in influencing how family life is regulated and organised
Title from publisher's bibliographic system (viewed on 21 Nov 2019)
Keywords: European Court of Human Rights; Fathers / Legal status, laws, etc / Europe; Parent and child (Law) / Europe